Optimisation of annealing temperature for low temperature processed inverted structure Caesium Formamidinium Lead Triiodide perovskite solar cells. (1st November 2019) - Haque, Faiazul; Yi, Haimang; Duan, Leiping; Zhang, Yu; Wright, Matthew; Conibeer, Gavin; Uddin, Ashraf
Abstract: Hybridization of Caesium and Formamidinium is considered as a promising approach to fabricate methylammonium-free perovskites for photovoltaic applications. Typically, Csx FA1-x PbI3 perovskite solar cells employ the normal device structure, which incorporates a high temperature processed rigid metal oxide layer as the electron transporting layer. This increases the cost of production and limits the use of Caesium-Formamidinium based perovskites for low temperature flexible substrates. In this study, we employed low temperature processed metal oxide free planar-heterojunction Caesium Formamidinium Lead Triiodide (Cs0.15 FA0.85 PbI3 ) perovskites in an inverted device structure and systematically investigated the role of post deposition annealing temperature on the film and device properties. The annealing temperature was varied from 130 °C to 170 °C. The film morphology and optical and charge extraction properties of devices is found to be highly dependent on the annealing temperature. The best average power conversion efficiency of 11.72% was obtained for 150 °C annealing temperature. These results show that determining the optimum post deposition annealing temperature is crucial to ensure successful charge extraction from the fabricated devices in order to achieve improved performance.